Pengembangan Bahan Ajar Botani Berbasis Kontekstual Dan Pendekatan SAVI (Somatis, Auditori, Visual, Intelektual) Untuk Meningkatkan Motivasi Dan Hasil Belajar Mahasiswa (LPPM UKI Toraja, 2019)
Students tend to interpret that the knowledge given will certainly have benefits for increasing their abilities and profession in the future, so of course students should be able to learn not only from lecturers but also from their experience and environment. In the lecture process, lecturers are often faced with problems when directing students to learn because each student has different learning styles. Therefore, to overcome the problem of diverse student learning styles, the researcher develops teaching materials that integrate contextual approaches with SAVI approaches (somatic, auditory, visual, and intellectual). The research aims to develop teaching materials that can improve student learning success. Development begins with a preliminary study, the design phase of teaching materials, the stage of development of teaching materials, and the validation phase of teaching materials. The results of the validation of teaching materials by the expert team showed a percentage value of 79%, which means the teaching material developed was included in the valid criteria and was suitable for use.